ANALISIS PENYERAPAN.TENAGA.KERJA SEKTOR KONSTRUKSI DI KABUPATEN/KOTA.PROVINSI JAWA.TIMUR TAHUN 2011-2015 - Fachreza, Achmad Naufal (Jurnal Ekonomi Pembangunan, 2017)
The purpose of this study was to determine how much influence of the total populations, GRDP, and minimum wage on the labor force absorption in the city district, East Java Province  in 2011-2015. Processing data using approach OLS (Ordinary Least Square) with taking best model is the random effect model with the auxiliary software Eviews 9 in operation. The results of this study is to show the variables of total populations has a positive effect on the labor force absorption with the coefficient value of  0.702167, which means when total population increased by 1%, the labor force absorption will increase by 0.70%. Variable GRDP has a positive effect on the labor force absorption with the coefficient value of  0.444610, which means when the GRDP increased by 1%, then the labor force absorption would increase by 0.44%. To a variable wage has a positive effect with the coefficient value of 0.376859  which means that any increase in wage value of Rp 1it will increase the labor force absorption to 0.38%.